Ascending Excitatory and Inhibitory Motor Activity of Colonic Longitudinal and Circular Muscles in Rat Model - Zornitsa Gorcheva; Galya Tz. Stavreva; Negrin Negrev; Radomir Radomirov (Journal of Biomedical & Clinical Research, 2019)
In this experiment we studied the role of excitatory and inhibitory neurotransmissions in the ascending reflex pathways in isolated rat colon. Partitioned organ bath, electrical field stimulation (EFS), drugs and isolated preparations were used to evaluate motor activity of (LM) and circular muscles (CM). Ascending motor responses of LM and CM were frequency-dependent contraction, significantly more expressed in LM. Atropine (0.3 µM) decreased ascending contractions of LM. During atropine treatment spantide (0.1 µM) further suppressed ascending contractile motor responses. In the presence of atropine, L-NNA (0.5 mM) restored ascending contractions of LM, while contractions were strongly depressed after addition of L-arginine (0.5 mM). Ascending response in CM, caused by atropine, consisted of an initial relaxation followed by contraction. Spantide decreased the contraction. L-NNA reduced the relaxation and significantly restored the atropine-influenced contraction, while L-arginine induced a deep relaxation of CM. The presence of ChAT, SP-containing nerve cell bodies and fibers and NADPH-diaphorase-reactive cell bodies and processes in myenteric ganglia were detected. The results indicated that nitric oxide is an important modulator of ascending cholinergic and tachykininergic excitation in colonic region of the large intestine of rats.